MICROALGAE BIOMASS PRODUCTIVITY BY CO2 INJECTION IN CORRELATION WITH pH VARIATION IN PHOTOBIOREACTOR - Onie Kristiawan (Scientific Contributions Oil and Gas, 2014)
Microalgae can bring solution for reducing CO2 and as alternative sustainable energy source. CO2reduction by microalgae was done by fi xation of CO2 during photosynthesis while they grow. The objectiveof the study is to get pH condition from CO2 injection into cultivated microalga that gives better productivityof biomass. Microalga that used was Scenedesmus.sp. Scenedesmus.sp did grown better in Walne media onlab scale experiments. CO2 injection as pH control that gave the highest dry weight obtained on pH rangevalue 7.0-7.5. As one of the controlling factor that determines the biological ability of microalgae in utilizingnutrient, pH value shows that at range of pH 8.0 – 8.5 and 9.0 – 9.5 can decrease photosynthetic process onmicroalgae Scenedesmus.sp Thus the highest fi xated CO2 also on pH value 7.0 – 7.5. This research give abrief explanation that in the range of pH 7.0 – 7.5 contain more CO2 than range pH 8.0 – 8.5 and 9.0 – 9.5.Culture temperature did not show any high fl uctuation at morning and in the mid-day of treatment.